2021
DOI: 10.3389/fpsyg.2021.678712
|View full text |Cite
|
Sign up to set email alerts
|

Morpho-Phonetic Effects in Speech Production: Modeling the Acoustic Duration of English Derived Words With Linear Discriminative Learning

Abstract: Recent evidence for the influence of morphological structure on the phonetic output goes unexplained by established models of speech production and by theories of the morphology-phonology interaction. Linear discriminative learning (LDL) is a recent computational approach in which such effects can be expected. We predict the acoustic duration of 4,530 English derivative tokens with the morphological functions DIS, NESS, LESS, ATION, and IZE in natural speech data by using predictors derived from a linear discr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 66 publications
2
12
0
Order By: Relevance
“…Critically, we find that when inflectional functions of [ɐ] serve as inputs to the learning network, uncertainty associated with these functions obtained from the network is a better statistical predictor for [ɐ]'s phonetic characteristics than when inflectional functions serve as outputs. Accordingly, the present study contributes to a line of research that investigates how uncertainty affects speech production through a combination of computational modeling of learning and an examination of the predictions of these models for the phonetic characteristics of actual speech (for example Baayen et al, 2019 ; Tomaschek et al, 2019 ; Tucker et al, 2019 ; Stein and Plag, 2021 ; Schmitz et al, 2021b in the present special issue).…”
Section: Introductionmentioning
confidence: 91%
“…Critically, we find that when inflectional functions of [ɐ] serve as inputs to the learning network, uncertainty associated with these functions obtained from the network is a better statistical predictor for [ɐ]'s phonetic characteristics than when inflectional functions serve as outputs. Accordingly, the present study contributes to a line of research that investigates how uncertainty affects speech production through a combination of computational modeling of learning and an examination of the predictions of these models for the phonetic characteristics of actual speech (for example Baayen et al, 2019 ; Tomaschek et al, 2019 ; Tucker et al, 2019 ; Stein and Plag, 2021 ; Schmitz et al, 2021b in the present special issue).…”
Section: Introductionmentioning
confidence: 91%
“…The representations and learning mechanisms that we are using in the present study have been found to be useful to predict behavioural data in previous work (e.g. Chuang et al, 2020b;Stein and Plag, 2021;Schmitz et al, 2021). We compare the measures extracted from the DLM with classical psycholinguistic predictors such as orthographic neighbourhood density.…”
Section: Introductionmentioning
confidence: 91%
“…This setup has been successful at predicting a range of behavioural data related to lexical processing (e.g. Chuang et al, 2020b;Stein and Plag, 2021;Schmitz et al, 2021;Chuang et al, 2022a;Gahl and Baayen, 2022;Cassani et al, 2019;Heitmeier and Baayen, 2020). To model trial-to-trial learning we make use of the Widrow-Hoff learning rule (Widrow and Hoff, 1960) which allows learning of real-valued semantic vectors.…”
Section: Computational Models Of Lexical Decisionmentioning
confidence: 99%
See 1 more Smart Citation
“…Discriminative learning process thus capture incremental, implicit learning, rather than explicit changes in perception or beliefs based on logic or reasoning (see e.g., Ramscar et al, 2013a;Nixon, Poelstra and van Rij, 2022), and can be formalised by training neural networks using virtually any computational learning algorithm that takes into account error during learning (though whether a model is discriminative or associative depends on the representation of cues and outcomes in the model, see Bröker and Ramscar, 2020). Because they are relatively simple to implement, and models based on them are easily interpreted, a number of recent psycholinguistic studies have made use of the learning equations proposed by Rescorla and Wagner (1972) to formalise learning problems and derive predictions about participants' behaviour during experiments in domains such as: word learning (Nixon, 2020;Ramscar et al, 2010;Ramscar, Dye, Popick and O'Donnell-McCarthy, 2011;Ramscar et al, 2013a), morphological structure learning in children (Ramscar et al, 2010(Ramscar et al, , 2011(Ramscar et al, , 2013b and adults (Arnon and Ramscar, 2012;Ramscar, 2013;Vujović, Ramscar and Wonnacott, 2021); morphological processing in adults (Baayen, Milin, Durdevic, Hendrix and Marelli, 2011;Tomaschek, Plag, Ernestus and Baayen, 2019;Nieder, Tomaschek, Cohrs and de Vijver, 2021); auditory comprehension and recognition (Arnold, Tomaschek, Sering, Lopez and Baayen, 2017;Shafaei-Bajestan and Baayen, 2018); effects of the lexicon on articulation (Tucker, Sims and Baayen, 2019;Tomaschek et al, 2019;Schmitz, Plag, Baer-Henney and Stein, 2021;Stein and Plag, 2021;Tomaschek and Ramscar, 2022); phonetic learning (Nixon, 2018(Nixon, , 2020Tomaschek, 2020, 2021); and the trial-by-trial changes in the neural signal that occur with learning…”
Section: Discriminative Learningmentioning
confidence: 99%